Bad luck and trouble - Child, Lee (Jack Reacher., 2008)
When a man is killed by being thrown from a helicopter high over the California desert, loner Jack Reacher discovers that someone is targeting his old friends and teammates and launches a personal campaign to end the conspiracy before it claims any more lives.